Edukasi Hukum Kesehatan bagi Pasien Mengenai Hak dan Kewajiban di Rumah Sakit - Yeni Vitrianingsih; Rahayu Mardikaningsih; Rommy Hardyansah (Universitas 45 Surabaya, 2025)
Health law education for patients and their families regarding their rights and obligations in hospitals. Lack of understanding of health law among patients and their families often triggers conflicts and disputes in hospitals. Although patients' rights are guaranteed by law, a lack of legal literacy makes it difficult to realize these rights in practice. This community service project proposes a comprehensive education model aimed at increasing patient and family awareness of their rights and obligations. This program will be implemented through several main stages: (1) an initial survey to identify educational needs; (2) the development of concise, practical, and easy-to-understand modules; (3) interactive educational sessions delivered directly in the hospital area; and (4) the distribution of easily accessible information materials. With this approach, our program not only focuses on empowering patients to be more proactive in medical decision-making but also aims to create a more transparent and harmonious relationship between patients, families, and healthcare professionals. It is hoped that the end result of this program will significantly reduce the potential for medical disputes and encourage the realization of more humane and patient-centered healthcare services.